2016
DOI: 10.1007/s40333-016-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

SOC storage and potential of grasslands from 2000 to 2012 in central and eastern Inner Mongolia, China

Abstract: Abstract:Grassland ecosystem is an important component of the terrestrial carbon cycle system. Clear comprehension of soil organic carbon (SOC) storage and potential of grasslands is very important for the effective management of grassland ecosystems. Grasslands in Inner Mongolia have undergone evident impacts from human activities and natural factors in recent decades. To explore the changes of carbon sequestration capacity of grasslands from 2000 to 2012, we carried out studies on the estimation of SOC stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Li et al [40] and Wang et al [41] have proposed that the content of nitrogen in the soil decreases gradually with the growth of the age of C. equisetifolia, and we got the same result. Organic matter is closely related to soil structure, aeration, permeability, and absorbability, and is one of the indexes of soil fertility [42,43]. Carter [44] reported that increasing soil organic matter content could significantly influence soil microbial diversity.…”
Section: N D Op H Y T I C C O L O N I Z a T I O N Is L I M I T E D T mentioning
confidence: 99%
“…Li et al [40] and Wang et al [41] have proposed that the content of nitrogen in the soil decreases gradually with the growth of the age of C. equisetifolia, and we got the same result. Organic matter is closely related to soil structure, aeration, permeability, and absorbability, and is one of the indexes of soil fertility [42,43]. Carter [44] reported that increasing soil organic matter content could significantly influence soil microbial diversity.…”
Section: N D Op H Y T I C C O L O N I Z a T I O N Is L I M I T E D T mentioning
confidence: 99%
“…Karst landforms are unique ecosystems that differ from non-karst areas and are characterized by low stability, poor self-regulation and low environmental capacity. The spatial distribution of SOC in karst areas is highly heterogeneous [17,18]. The spatial heterogeneity of SOC and the ecological environment in karst areas is much greater than in non-karst areas [19].…”
Section: Introductionmentioning
confidence: 99%
“…Karst areas are unique ecosystems that differ from non-karst areas in terms of terrain and landforms because of the special geological and climatic conditions that lead to karst mountainous areas exhibiting low environmental capacity, low stability and poor self-regulation [12,13]. In different karst regions of Guizhou, the soil environment is coupled with a high rate of rock exposure and a noncontinuous soil layer, and the microtopography is complex, which leads to the development of noncontinuous shallow soil with varying thickness.…”
Section: Introductionmentioning
confidence: 99%